2014
DOI: 10.3390/ijms151019253
|View full text |Cite
|
Sign up to set email alerts
|

DRAM1 Protects Neuroblastoma Cells from Oxygen-Glucose Deprivation/Reperfusion-Induced Injury via Autophagy

Abstract: DNA damage-regulated autophagy modulator protein 1 (DRAM1), a multi-pass membrane lysosomal protein, is reportedly a tumor protein p53 (TP53) target gene involved in autophagy. During cerebral ischemia/reperfusion (I/R) injury, DRAM1 protein expression is increased, and autophagy is activated. However, the functional significance of DRAM1 and the relationship between DRAM1 and autophagy in brain I/R remains uncertain. The aim of this study is to investigate whether DRAM1 mediates autophagy activation in cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Other identified variants point to genes involved in autophagy and apoptotic processes , such as DRAM1 and F0X03 , both related to brainstem volumes. DRAM1 encodes a lysosomal membrane protein involved in activating TP53-mediated autophagy and apoptosis, 60 and mouse models mimicking cerebral ischemia and reperfusion have found that inhibiting the expression of DRAM1 worsens cell injury 61 . The most significant variant located 9Kb downstream from DRAM1 was also associated with a CpG site proximate to active TSS upstream of that gene in several mature brain tissues (Table S5 and Figure S3.B).…”
Section: Discussionmentioning
confidence: 99%
“…Other identified variants point to genes involved in autophagy and apoptotic processes , such as DRAM1 and F0X03 , both related to brainstem volumes. DRAM1 encodes a lysosomal membrane protein involved in activating TP53-mediated autophagy and apoptosis, 60 and mouse models mimicking cerebral ischemia and reperfusion have found that inhibiting the expression of DRAM1 worsens cell injury 61 . The most significant variant located 9Kb downstream from DRAM1 was also associated with a CpG site proximate to active TSS upstream of that gene in several mature brain tissues (Table S5 and Figure S3.B).…”
Section: Discussionmentioning
confidence: 99%
“…40 This existing model could mimic extracellular conditions in cerebral ischemia and subsequently reperfusion, and is commonly used as a model for in vitro research. 41 In brief, to induce OGD/R injury, cultured primary human astrocytes were cultured in 12-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…DRAM1, DNA damage regulated autophagy modulator 1, was reported to increase autophagy flux through promoting lysosomal acidification and protease activation [ 37 ]. It was found that DRAM1 knockdown inhibited autophagy flux and aggravated cell injury in Neuro-2a cells [ 38 ]. A recent study has shown that CLs induced cell necrosis involved in late-stage autophagic flux inhibition [ 39 ].…”
Section: Discussionmentioning
confidence: 99%